The Impact of 30-Degree Head-Up Position on Cerebral Perfusion in Moderate Brain Injury Patients - Basuki, Pinky Issabella Nanda; Siswoyo; Rondhianto; Mustakim (Jurnal Kegawatdaruratan Medis Indonesia, 2024)
Background: Nursing problems in brain injury patients include the risk of ineffective perfusion due to reduced oxygen flow to the brain, which, if not treated immediately, will increase intracranial pressure (ICP). One way to increase ICP is with 30-degree head-up position intervention. Objective: This study aimed to analyze the application of 30-degree Head Up Position on Cerebral Perfusion in Moderate Brain Injury Patients. Method: This research is an observational study with a case study design. Primary data was obtained through anamnesis and physical assessment with a sample of a patient being treated in the Hospital by assessing the effect of the 30-degree head-up position carried out for 30 minutes for 3 consecutive days. Results: In this study, the results showed an increase in cerebral perfusion as indicated by cerebral perfusion indicators, namely blood pressure, MAP, pulse, patient breathing improved, and the patient's level of consciousness increased until the final evaluation. Conclusion: From the results of the innovation analysis in this case, providing a 30-degree head-up position in patients with a risk of ineffective cerebral perfusion is one form of effectiveness in increasing the patient's cerebral perfusion so that it can prevent an increase in intracranial pressure.